2009
DOI: 10.1177/0163278709338558
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Fennell Phases to Symptoms Among Patients With Chronic Fatigue Syndrome

Abstract: The Fennell Phase Inventory (FPI) is an instrument designed to measure phases of the illnesses known as Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). The current study explored how the FPI was related to physical and psychological functioning as well as coping style. Based on FPI scores, 111 adults with ME/CFS were placed in one of three groups: crisis, stabilization, or resolution. Results showed that the crisis group demonstrated significantly worse functioning than at least one other group fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…Whereas previous research found that fatigue and pain severity seemed to be the same across the phases of chronic fatigue syndrome (CFS) [68], our findings indicate that for persons with PIFS, the symptom severity may vary in different phases. Our participants described that fatigue increased during the downward phase and that it was at its worst during the turning phase; for some, the fatigue abated during the upward and chronic phases.…”
Section: Discussioncontrasting
confidence: 93%
“…Whereas previous research found that fatigue and pain severity seemed to be the same across the phases of chronic fatigue syndrome (CFS) [68], our findings indicate that for persons with PIFS, the symptom severity may vary in different phases. Our participants described that fatigue increased during the downward phase and that it was at its worst during the turning phase; for some, the fatigue abated during the upward and chronic phases.…”
Section: Discussioncontrasting
confidence: 93%
“…Those with a longer illness duration may have learned more effective coping skills such as planning and acceptance compared to the shorter illness duration group [17]. This supports previous findings that patients with CFS endure a “crisis” stage early in their illness [6], where they experience emotional distress and may be overwhelmed by the challenges of this debilitating illness [33]. …”
Section: Discussionsupporting
confidence: 76%
“…Although the less adaptive coping styles observed in the short duration group resembled the patterns of coping found by Reynolds, et al (2009) in the “crisis” phase group, Reynolds, et al did not find a significant relationship between illness duration and illness phase. As noted earlier, people with this illness may return to the “crisis” phase during periods of relapse, regardless of how long they have been ill.…”
Section: Discussionmentioning
confidence: 82%
“…Jason, Fennell, Klein, Fricano, and Halpert (1999) suggest that patients with chronic fatigue syndrome experience an initial “crisis” phase characterized by entering into a state of emotional distress after the initial onset of the illness or during a period of relapse. Those in the crisis phase of the illness are more likely to use maladaptive coping styles than those in other phases of the illness (Reynolds, Brown, & Jason, 2009). However, Reynolds, et al, found no relationship between illness phase and illness duration, in developing this illness phase model, Jason, et al recognized that patients may move out of the crisis phase and return during a relapse, suggesting that the relationship between illness duration and illness phase is not necessarily linear.…”
mentioning
confidence: 99%